Beyond the chronic pain stage: default mode network perturbation depends on years lived with back pain - Heukamp, Nils; Moliadze, Vera; Mišić, Mina; Usai, Katrin; Löffler, Martin; Flor, Herta; Nees, Frauke (Pain, 2025)
Research has indicated that the default mode network (DMN) is perturbated in patients with chronic pain when compared with healthy controls, and this perturbation is correlated with the duration of pain during the chronic pain stage. It remains unclear whether DMN adaptations manifest during the subacute pain stage and progress over time because of the duration of pain experience, rather than being a specific correlate of the chronic pain stage. Furthermore, information regarding whether these adaptations are related to cognitive processes of adaptation is lacking. To this end, we examined the DMN in 31 patients with chronic back pain (CBP), 77 patients with subacute back pain (SBP), as well as 39 healthy pain-free controls (HC) applying a graph-theoretic network approach on functional resting-state magnetic resonance imaging. Beyond the comparison between groups, we used a linear analysis considering the years lived with pain (YLP) across all patients with back pain and additionally performed a mediation analysis of the role of cognitive pain coping. In line with previous studies, we found significant DMN perturbation in CBP compared with HC. However, this did not apply to the comparison of CBP with SBP. Instead, we observed a positive correlation between DMN perturbation and YLP. This was significantly mediated by coping attitudes towards pain. Default mode network perturbation may thus reflect neural adaptation processes to pain experience rather than a single correlate of the chronic pain stage and be modulated by cognitive adaption. This points to potentially underinvestigated significant adaptation processes that could enable more fine-grained patient stratification.
Gesehen am 28.07.2025